RECONSTRUCTION OF MAQASID SHARIAH VALUES IN ISLAMIC RELIGIOUS EDUCATION LEARNING AS A BASIS FOR MODERATE CHARACTER FORMATION - Galby Silvia Rachmah; Moh. Mahrus; Umar Fauzan; Abzar Duraesa (Academic Bright Collaboration, 2026)
This study aims to reconstruct Islamic Religious Education (PAI) learning through the integration of Ibn ‘Ashur’s Maqasid Shariah values as a foundation for strengthening students’ moderate character in madrasa education. This study employed a qualitative case study approach at MTs Maarif NU Sindang Sari involving PAI teachers, students, and school administrators selected through purposive sampling. Data were collected through semi-structured interviews, participatory observations, and documentation analysis, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that Ibn ‘Ashur’s Maqasid Shariah values, namely al-Fitrah, al-Samahah, al-Musawah, and al-Hurriyah, have been implicitly implemented through religious habituation, ASWAJA local content, dialogical learning, and inclusive school culture. The study also found that the four pillars of Nahdlatul Ulama function as cultural bridges for contextualizing Maqasid Shariah values within the madrasa ecosystem. However, the implementation remains informal and has not yet been systematically integrated into curriculum documents and assessment systems. This study contributes to the development of transformative Islamic education by positioning Maqasid Shariah as a pedagogical framework for moderate character formation. However, the research was limited to a single madrasa context, which may restrict the broader generalization of the findings. This study offers originality by operationalizing Ibn ‘Ashur’s contemporary Maqasid Shariah within PAI learning and connecting it with Nahdlatul Ulama’s cultural traditions as a contextual model for moderation-oriented Islamic education.